REPOSISI KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM TATANAN PENYELENGGARAAN BEREGARA - Surahman Surahman (Maleo Law Journal, 2018)
State administration in the Unitary State of the Republic of Indonesia shall be implemented in accordance with the Constitution of the State of the Republic of Indonesia Year 1945. The 1945 Constitution has been amended four times. One of the fundamental changes is the change of Article 1 paragraph (2) which previously reads "Sovereignty is in the hands of rakayat and is fully implemented by the People's Consultative Assembly" which then turns into Sovereignty in the hands of the People and is implemented according to the Constitution " influencing the regulatory arrangement of laws in Indonesia as regulated in Article 7 aaaayat (1) of Law Number 10 Year 2004 concerning the procedure for the formulation of the Laws and Regulations, which does not place any MPR Decrees in the order of the Laws and Regulations. The decision of the MPR is one of the juridical instruments capable of bridging the norms of the Constitution which are general to the norms of the existing Law below, in addition the MPR Decree also plays a significant role in determining the state of the country. Keyword :  Reposition of MPR Decree, State practice.